Rebirth of childbirth: reflections on medicalization of the Brazilian obstetric care - Samara Calixto Gomes; Lívia Parente Pinheiro Teodoro; Antonio Germane Alves Pinto; Dayanne Rakelly de Oliveira; Glauberto da Silva Quirino; Ana Karina Bezerra Pinheiro
ABSTRACT Objective: to reflect on the medicalization process of childbirth and birth and its consequences based on a Brazilian audiovisual media artifact. Method: reflective and interpretive analysis of the documentary O Renascimento do Parto (The Rebirth of Childbirth) based on Critical Discourse Analysis. Results: c-section emerges as an alternative to adverse conditions of pregnancy. However, it has become a routine and abusive practice of a medicalized obstetric care, thus becoming a social problem. In order to the incidence of c-sections decrease, women's protagonism must be restored, in addition to considering psychological, affective, emotional, spiritual, cultural, and contextual aspects in childbirth. Conclusion: childbirth is established as a material element and a mental phenomenon of social practices. We must interrupt the predominant model, allowing the body to express itself through the release of oxytocin, and decrease the segregation that c-section causes, thus enabling affective bonds.